Thermal-Hydraulic calculations for the Westinghouse AP-1000 clean core with MITH code - Malatim, Tariq Zakariya; Dakhil, Amal (Sharwes Scientific Journal, 2025)
In this study, the core of the Westinghouse AP1000 reactor [1] gen. III+ was simulated, which is one of four reactors that have been nominated to be adopted by the Libyan Atomic Energy Establishment [2]. The MITH code, which is a thermal-hydraulic code, is used to find the clean core thermal parameters. The power distribution in the reactor core was evaluated using the 2DB code [3]. The hottest assemblies, which have the maximum power production were determined with a value of 30.82 MW Using 2DB code, the hottest assembly has been described, and the hottest channels have been found. The power produced in the hottest channel is 139 KW. Using the MITH code [4], the parameters of fuel elements were evaluated for average and hottest channel length, which were divided into 40 meshes for drawing and 100 meshes for studying. The temperatures of the fuel center & surface, clad, and coolant have been determined and they were satisfactory, while the minimum DNBR has been found to be within safe limits with a value of 2.17.